THE APPROACH OF THE LITHUANIAN COURTS TO THE INTERNATIONAL STATE IMMUNITY LAW - Zaleskis, Julius (Teisė, 2015)
Uncertainty in international state immunity regulation causes a variety of states’ approaches to this area of international law. The article aims to reveal the approach to the international state immunity doctrine that is taken by the Lithuanian courts. The state immunity doctrine is essentially considered in Lithuania as an area of national law established by the case law of national courts. The reasoning of the Lithuanian courts implies that they treat the state immunity doctrine as a matter of Lithuania’s choice rather than binding international law. The Lithuanian courts tend to ignore international customs and other sources of international state immunity law. In most of the cases, application of the state immunity doctrine in Lithuania is non-compliant with the international law, limiting the immunity of state in its particular private activities, as well as requiring for the assessment of the nature of the activities of a defendant state. In a few state immunity cases Lithuanian courts analysed the nature of foreign states’ activities essentially in line with international law. The approach of the Lithuanian courts to the international state immunity law may result in international responsibility of Lithuania. The Lithuanian courts’ approach can be criticized from the national constitutional perspective, treating international customary law as a legal source in Lithuania. However, the sceptic Lithuanian approach to the international state immunity law is not unique in terms of practice of foreign states.